Staging resection of multiple primary esophageal cancer by endoscopic submucosal dissection and esophagectomy: A case report. Issue 18 (May 2018) - Yao, Yufeng; Wu, Yimin; Chai, Ying
Abstract: Rationale: Multiple primary esophageal cancer pose great risks to patients and are always challenging to resect surgically. In order to reduce the risk of postoperative complication and meet the needs of minimally invasive and precision medicine, new treatment plans have been always developed for patients with multiple primary esophageal cancer. Patient concerns: A 75-year-old man was admitted to our hospital for aggravated dysphagia. No significant abnormalities were identified on physical examination. Diagnoses: Endoscopic examination detected 3 masses in the esophagus and biopsy confirmed multiple primary esophageal cancer. Intervention: The patient received a new staging treatment procedure firstly and an innovative single-position, minimally invasive Ivor Lewis esophagectomy in our hospital. Outcomes: This patient discharged one week after the surgery and enjoyed a good health during our follow up for 30 month. Lessons: We believe our procedure provides a beneficial new alternative approach for patients with multiple primary esophageal cancer.